RFID Based Employee Attendance System Design on CV. Sachio Express Sejahtera - Nanda Ihsan Pradana Rian Kusuma; Widiati, Ina Sholihah Widiati; Setiyawan, Muhammad Setiyawan (Formosa Journal of Computer and Information Science, 2023)
CV. Sachio Express Sejahtera is a registered expedition company located in Surakarta. Attendance is the most crucial aspect for the company as it affects an employee's salary based on attendance data. Therefore, the presence of a real-time attendance system stored in a database is highly needed. The design of the employee attendance system utilizes the Rapid Application Development (RAD) method, which includes requirements planning, system design, development processes, and implementation. This method is employed to meet user needs and achieve desired outcomes.The result of the design for the employee attendance system is the utilization of RFID (Radio Frequency Identification) cards as a tool for attendance record. It is expected that this system will assist employees in recording their attendance and reduce any potential data manipulation or inaccuracies